2015
DOI: 10.1136/archdischild-2015-309259
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease in the ERA of the new ESPGHAN and BSPGHAN guidelines: a prospective cohort study

Abstract: On the basis of this prospective study, diagnosis of CD can be reliably performed without a duodenal biopsy in approximately 11% of cases. At least during a medium-term follow-up, this approach has no negative consequences relating to clinical remission, adherence to diet, and quality of life of children with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…Even though CD can be reliably diagnosed following the latest ESPGHAN and BSPGHAN guidelines [16], as not all diagnostic procedures required by the new guidelines are available in all countries, our results may suggest to further simplify the new ESPGHAN guidelines. As a matter of fact, it is not useful nor necessary to perform an expensive determination, such as HLA, as in all patients with tTG higher than 10 x ULN who had HLA heterodimer determined it was compatible with CD.…”
Section: Discussionmentioning
confidence: 97%
“…Even though CD can be reliably diagnosed following the latest ESPGHAN and BSPGHAN guidelines [16], as not all diagnostic procedures required by the new guidelines are available in all countries, our results may suggest to further simplify the new ESPGHAN guidelines. As a matter of fact, it is not useful nor necessary to perform an expensive determination, such as HLA, as in all patients with tTG higher than 10 x ULN who had HLA heterodimer determined it was compatible with CD.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, the British Society of Paediatric Gastroenterology, Hepatology and Nutrition (BSPGHAN) also reviewed its diagnostic guidelines for CD, reaching similar conclusions [21]. A very recent prospective study showed that diagnosis of CD can be reliably performed without a duodenal biopsy in approximately 11% of cases, selected applying the ESPGHAN/BSPGHAN guidelines in a restricted way, considering as symptomatic only those cases with diarrhoea, weight loss, failure to thrive and iron deficiency anaemia [22]. However, some studies suggest prudence in omitting performance of a duodenal biopsy in these children.…”
Section: Discussionmentioning
confidence: 99%
“…Benelli et al. adopted a very strict definition of what is meant by a symptomatic patient . Only children with diarrhoea and weight loss, failure to thrive or sideropenic anaemia were classified as symptomatic.…”
Section: Discussionmentioning
confidence: 99%